A preliminary study on the residue of carbofuran in sweet potato in Perlis / Harbant Singh, Mohamad Idiris Saleh and Putri Ibrizah Zahariman - Singh, Harbant; Saleh, Mohamad Idiris; Zahariman, Putri Ibrizah (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
The aim of this research was primarily to identify the correct dose of Furadan, a systemic pesticide, in the control of sweet potato weevil. Different doses of the chemical, viz., 0, 0.5, 1.0, 1.5, 2.0, 2.5, and 3.0 kg a.i. Furadan 3 G / ha, were applied to the soil, and their effects on the yield and residue in the plant and soil were investigated. Gas chromatography was used in the residue studies. The solid phase extraction method, a modification of the techniques used by Beachamo ef a/, and Getzin et al. in 1989, was used in isolating pure carbofuran (to be used for the preparation of standard solution for residue analysis) from the commercial product, Furadan 3 G. No residue was detected from sweet potato tubers treated with different doses of the chemical. However, carbofuran persisted in soils from polybags for 30 days. The rate 1.5 kg a.i. / ha, showed a phytotonic effect on tuber formation and a highest average yield in Empat Bulan (yellow-flesh variety of sweet potato). It also recorded the lowest Cylas damage of 15% in Serdang 1 variety, when compared to the 50% damage in the no chemical treatment. Hence, it could be selected as one of the pesticides in the control of Cylas sp. in sweet potato.